Liver‐related mortality and hospitalizations attributable to chronic hepatitis C virus coinfection in persons living with HIV. Issue 9 (23rd February 2017) - Mena, A; Meijide, H; Rodríguez‐Osorio, I; Castro, A; Poveda, E
Abstract : Objectives: The aim of this study was to compare liver‐related mortality and liver‐related hospitalizations for persons living with HIV (PLWH) with and without hepatitis C virus (HCV) exposure, and to estimate the fraction of liver disease attributable to chronic HCV coinfection. Methods: An ambispective cohort study followed PLWH between 1993 and 2014. PLWH were classified into three groups: those who were HIV‐monoinfected, those who cleared HCV spontaneously and those with chronic HCV coinfection. Liver‐related mortality was estimated for the three groups and compared with the adjusted standardized mortality ratio. Results: Data for 2379 PLWH were included in the study (1390 monoinfected individuals, 146 spontaneous HCV resolvers and 843 with chronic HCV coinfection). Global mortality was 33.8%, 21.4% of which was liver‐related. Patients who died from liver‐related causes were mostly on antiretroviral therapy and had an undetectable HIV viral load when they died. The liver‐related mortality rate in those with chronic HCV coinfection was 10.01 per 1000 patient‐years vs . 3.84 per 1000 patient‐years in the HIV‐monoinfected group ( P < 0.001). The adjusted standardized mortality ratio in the chronically HCV‐coinfected group was 4.52 (95% confidence interval 2.98–5.86). The fractions of liver‐related mortality and liver‐related hospitalizations attributable to chronic HCV coinfection were 0.61 and 0.74, respectively. There were no differences in liver‐related events between HIV‐monoinfected individuals and those who spontaneously cleared HCV. Conclusions: Chronic HCV infection increases the risk of liver‐related mortality and liver‐related hospitalizations in PLWH, despite good control of HIV infection. Sixty per cent of liver‐related mortality in chronically HCV‐coinfected PLWH could be attributable to chronic HCV infection. The effect of mass HCV eradication with new therapies should be evaluated.